2019
DOI: 10.1002/ece3.5383
|View full text |Cite
|
Sign up to set email alerts
|

From canopy to seed: Loss of snow drives directional changes in forest composition

Abstract: Climate change is altering the conditions for tree recruitment, growth, and survival, and impacting forest community composition. Across southeast Alaska, USA, and British Columbia, Canada, Callitropsis nootkatensis (Alaska yellow‐cedar) is experiencing extensive climate change‐induced canopy mortality due to fine‐root death during soil freezing events following warmer winters and the loss of insulating snowpack. Here, we examine the effects of ongoing, climate‐driven canopy mortality on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 71 publications
(136 reference statements)
1
5
0
Order By: Relevance
“…A greater proportion of populations in decline occur on gentle slopes while healthy populations are more frequently found on steeper slopes (24°-40°) (Wooton & Klinkenberg, 2011). Soil saturation could be a factor on the flatter areas, creating stands with open canopies and shallow roots (Hennon et al, 2016) and shifts in community composition and stand dynamics can be expected (Bisbing et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A greater proportion of populations in decline occur on gentle slopes while healthy populations are more frequently found on steeper slopes (24°-40°) (Wooton & Klinkenberg, 2011). Soil saturation could be a factor on the flatter areas, creating stands with open canopies and shallow roots (Hennon et al, 2016) and shifts in community composition and stand dynamics can be expected (Bisbing et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported that yellow-cedar mortality is higher in open-canopy forests at low elevations with typically wet soils, or on shallow soils over bedrock (Hennon et al 1990, Schaberg et al 2005 (Comeau et al, 2019). As climate change results in this loss of mature, seed-D r a f t producing trees of a particular species, restructuring of forest communities over large regions may be observed (Bisbing et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…More frequent freeze–thaw events associated with warming winters can alter couplings between plant nutrient uptake, microbial communities, and nutrient cycling that ultimately lead to increased soil N and the potential for P leaching (Wipf et al 2015 ). Freeze–thaw events associated with transitions from snow to rain are additionally driving sudden shifts in forest community composition (e.g., yellow cedar Callitropsis nootkatensis replacement by western hemlock Tsuga heterophylla ; Oakes et al 2014 , Bisbing et al 2019 ). These shifts can in turn influence soil N cycling rates (Bisbing and D'Amore 2018 ) although total nutrient stocks may change more slowly.…”
Section: Terrestrial Production and Delivery Of Materials To Surface Watersmentioning
confidence: 99%
“…1880) and expansion (ca. 1925) of YC dieback throughout Southeast Alaska and British Columbia (Hennon et al 1990a;D'Amore and Hennon 2006;Stan et al 2011;Wooton and Klinkenberg 2011;Oakes et al 2014;Hennon et al 2016;Bisbing et al 2019;Comeau et al 2019).…”
Section: Dating the Onset Of Yellow-cedar Declinementioning
confidence: 99%